Nutritional counseling with or without systematic use of oral nutritional supplements in head and neck cancer patients undergoing radiotherapy. Issue 1 (January 2018) - Cereda, Emanuele; Cappello, Silvia; Colombo, Sara; Klersy, Catherine; Imarisio, Ilaria; Turri, Annalisa; Caraccia, Marilisa; Borioli, Valeria; Monaco, Teresa; Benazzo, Marco; Pedrazzoli, Paolo; Corbella, Franco; et al.
Abstract: Background: To evaluate the benefit of oral nutritional supplements (ONS) in addition to nutritional counseling in head and neck cancer (HNC) patients undergoing radiotherapy (RT). Methods: In a single-center, randomized, pragmatic, parallel-group controlled trial (ClinicalTrials.gov: NCT02055833; February 2014–August 2016), 159 newly diagnosed HNC patients suitable for to RT regardless of previous surgery and induction chemotherapy were randomly assigned to nutritional counseling in combination with ONS ( N  = 78) or without ONS ( N  = 81) from the start of RT and continuing for up to 3 months after its end. Primary endpoint was the change in body weight at the end of RT. Secondary endpoints included changes in protein-calorie intake, muscle strength, phase angle and quality of life and anti-cancer treatment tolerance. Results: In patients with the primary endpoint assessed (modified intention-to-treat population), counseling plus ONS ( N  = 67) resulted in smaller loss of body weight than nutritional counseling alone ( N  = 69; mean difference, 1.6 kg [95%CI, 0.5–2.7]; P  = 0.006). Imputation of missing outcomes provided consistent findings. In the ONS-supplemented group, higher protein-calorie intake and improvement in quality of life over time were also observed ( P  < 0.001 for all). The use of ONS reduced the need for changes in scheduled anti-cancer treatments (i.e. for RT and/or systemic treatment dose reduction or complete suspension, HR=0.40 [95%CI, 0.18–0.91], P  = 0.029). Conclusion: In HNC patients undergoing RT or RT plus systemic treatment, and receiving nutritional counseling, the use of ONS resulted in better weight maintenance, increased protein-calorie intake, improved quality of life and was associated with better anti-cancer treatment tolerance.